The 21st Century Skills Included in family Education and Life Skills Course for the Secondary Stage - Alzubaidi, Amani Hashim; Alarfaj, Abeer Mohammed (Journal of Curriculum and Teaching Methodology, 2023)
The research aimed at identifying the degree of including the 21st century skills in the life skills and family education course for the secondary stage. The study adopted the descriptive research approach represented by content analysis approach, to measure the objectives, activities, and assessment questions in the course. To achieve the purpose of the study, the researcher developed a content analysis card that included 3 major domains of the 21st century skills as stated by the Partnership for 21st Century Learning. The domains were distributed as following: learning and innovation skills, digital culture skills, and profession and life skills. The analysis card included 71 indicators. The results of the study showed that the mean percentage score of the inclusion of the 21st century skills in the life skills and family education skills was 33.33%, which is a low degree. The degree of the inclusion of the 21st century skills in the course objectives was 13.08%, which is a very low degree, the degree of the inclusion of the 21st century skills in course activities was 48.31%, which is a moderate degree, and the degree of the inclusion of the 21st century skills in the course assessment questions was 37.82%, which is a low degree. In the light of the research results, the researcher recommends the necessity of increasing the attention of the educational experts and those in charge of course planning to reconsider the content of the life skills and family education course for the secondary stage, so the inclusion of the 21st century skills is processed, organized, and improved, and the variation in the degree of their inclusion in the course is processed.